Monetary Policy Shocks and Narrative Restrictions: Rules Matter - Efrem Castelnuovo; Giovanni Pellegrino; Laust L. Særkjær (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Imposing restrictions on policy rule coefficients in vector autoregressive (VAR) models enhances the identification of monetary policy shocks obtained with sign and narrative restrictions. Monte Carlo simulations and empirical analyses for the United States and the Euro area support this result. For the U.S., adding policy coefficient restrictions yields a larger and more precise short-run output response and more stable Phillips multiplier estimates. Heterogeneity in output responses reflects variation in systematic policy reactions to output. In the Euro area, policy coefficient restrictions sharpen the identification of corporate bond spread responses to monetary policy shocks.
Keywords: C32; E32; E52; 330; monetary policy shocks; narrative restrictions; policy coefficient restrictions; vector autoregressive models; Monte Carlo simulations; DSGE models